Machine-readable Northern Karelian Proper-Livvi bilingual translation dictionary - Rantakaulio, Timo; Rueter, Jack; Pirinen, Flammie A.; Alnajjar, Khalid; Hämäläinen, Mika (Zenodo, 2022)
This machine readable bilingual translation dictionary of Northern Karelian Proper (ISO-639: krl) to Livvi aka Olonets-Karelian (ISO-639 olo) was created by Timo Rantakaulio during Google Summer of Code 2021 at Apertium. His work was facilitated through an online back-end dictionary editing tool `https://akusanat.com/verdd' with translation suggestions generated by Khalid Alnajjar and Mika Hämäläinen developers of the Verdd editor. Workflow, coordination, instruction and advice were given by Flammie A. Pirinen and Jack Rueter.